Optimizing the Use of Arbuscular Mycorrhizal Fungi and Bio-organic to Produce Quality Jernang (Daemonorops draco) Seeds as a Support for Community Economy - Purwati, Betty; Pertiwi, Hutami Indah; Aufa, Muhammad Agus (Journal of Tropical Silviculture, 2024)
Jernang rattan is produced from a palm species surface layer of fruit by resine with dark red. Jernang rattan cultivation has several obstacles due to limiteation of seed availability, low seed production, recalcitrant seeds, and slow seedling growth. In order to accelerate seedling growth and providing a good quality of seedlings, an inoculation of seedling with Arbuscular Mycorrhizal Fungi (AMF) and addition of bio-organics in growing media is needed. This study aimed to analyze the growth responses of Daemonorops draco Blume seedlings inoculated by AMF and addition of bio-organic. The research design used was completely randomized design which consists of two factors, AMF (M) consists of four levels (M0 = Without AMF, M1= AMF collection in the mycorrhizal laboratory M2= Indigenous FMA from rattan rhizosphere and bio-organic (B) consisting of five levels (B0= Without bio-organic, B1= dose of bio-organic 5%, B2= dose of bio-organic 10%, B3= dose of bio-organic 15%, B4= dose of bio-organic 20%). The results showed that control soil media could not to support the growth of Rattan Jernang Seedlings. The plant treated by interaction (M2B2) increased plant height by 140.76%, diameter by 106.57% and biomass by 591.22% compared with control. Keywords: AMF, Bio-organik, Daemonorops draco Blume, Seedling growth